“El caso Berciani” de Alan Pauls: un viaje a los bajos fondos - Rubio Gijón, Pablo (Acta Hispanica, 2016)
“El caso Berciani” (1992) relates to the genre of detective and mystery fiction by parody and distortion. Alan Pauls (Buenos Aires, 1959) explores the relation between order and abjection. In so doing, “El caso Berciani” becomes a thorough reflection on the failure of modernization. This article explores how this short story uses detective fiction to elaborate on knowledge and interpretation, and urban dystopias and social tensions.